KURANGNYA KONSUMSI BUAH DAN SAYUR SEBAGAI FAKTOR RISIKO KEJADIAN OVERWEIGHT PADA REMAJA PUTRI (STUDI PADA MAHASISWI FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS DIPONEGORO SEMARANG) - Awaliya, Henu Bey Putri; Pradigdo, Siti Fatimah; Nugraheni, Sri Achadi (Fakultas Kesehatan Masyarakat, 2020)
Youth groups have several problems such as consumption of fruits and vegetables that are less and overweight problems, so that adolescents can maintain their health, it is necessary to increase consumption of fruits and vegetables. The purpose of this study was to analyze the consumption of fruit and vegetables that are lacking as a risk factor for overweight among adolescent girls in FKM Undip Semarang class of 2018. This study uses an observational analytic type and a quantitative approach with a case-control design, as for sampling using a purposive sampling technique with total a sample of 84 research subjects. BMI data is taken by measuring the height and weight of research subjects. Data on fruit and vegetable consumption practices were obtained using FFQ sheets and 24-hour Food Recall sheets. For bivariate analysis using the chi-square test. The results showed that the number of servings of fruit consumption (p = 0.815) and the number of servings of vegetable consumption (p = 0.500) were not risk factors for overweight events. The results of this study also showed that the frequency of fruit consumption (p = 0.019; OR = 3.700; Cl 95% = 1.192-11.48) and the frequency of vegetable consumption (p = 0.023; OR = 3.333; Cl 95% = 1.14 - 9.72 ) can be said to be a risk factor for overweight events. It is expected that young women (female students) can apply the basic knowledge of nutrition that has been accepted to college and can increase the frequency of consumption of fruits and vegetables to prevent the incidence of overweight in adolescence.